Direct and ozone‐mediated forcing of the Southern Annular Mode by greenhouse gases. Issue 24 (16th December 2014) - Morgenstern, Olaf; Zeng, Guang; Dean, Sam M.; Joshi, Manoj; Abraham, N. Luke; Osprey, Annette
Abstract We assess the roles of long‐lived greenhouse gases and ozone depletion in driving meridional surface pressure gradients in the southern extratropics; these gradients are a defining feature of the Southern Annular Mode. Stratospheric ozone depletion is thought to have caused a strengthening of this mode during summer, with increasing long‐lived greenhouse gases playing a secondary role. Using a coupled atmosphere‐ocean chemistry‐climate model, we show that there is cancelation between the direct, radiative effect of increasing greenhouse gases by the also substantial indirect—chemical and dynamical—feedbacks that greenhouse gases have via their impact on ozone. This sensitivity of the mode to greenhouse gas‐induced ozone changes suggests that a consistent implementation of ozone changes due to long‐lived greenhouse gases in climate models benefits the simulation of this important aspect of Southern Hemisphere climate.